Victims of Child Sexual Violence from a Legal Perspective - Widya Romasindah Aidy; Mochammad Syafruddin Rezky Sanaky (Jurnal Hukum Sasana, 2022)
Law enforcement officers give appropriate punishments to perpetrators of sexual violence, so that the rule of law is truly enforced and order is created in society. Sanctions are intended to provide a deterrent effect for perpetrators of sexual violence so as not to repeat their behavior and prevent others from committing the crime because of the threat of severe punishment. The purpose of this study is to find: 1) children who are victims of criminal acts of sexual harassment; 2) the impact of children as victims of crimes of sexual violence; and 3) efforts to tackle crimes of sexual violence against children. The results of the study are as follows: efforts to overcome crimes of sexual violence against children are the role of parents who play an important role in protecting children from the risk of sexual violence; legal care as well as psychological rehabilitation support and psychological services for both children and their parents; and the role of the community to ensure the protection of children; also the role of the State, in the form of rehabilitation, which is an integrated process of treatment activities by restoring the child's condition. Rehabilitation in question is a process of organizing physical, mental, and social rehabilitation activities in an integrated manner so that the child can continue to carry out his social functions and skills in social life.